Bismuth Gadolinium Oxychloride with a Remarkable Visible‐Light‐Responsive O2 Evolution Activity Promoted by Iodine Doping. Issue 68 (7th October 2022) - Zhao, Conghui; Sun, Liwei; Xu, Yang; Dong, Beibei; Luo, Yuhong; Li, Jingde; Chen, Jianxin; Zhang, Zisheng
Abstract: Visible‐light‐responsive bismuth‐based oxyhalide has recently attracted extensive attention, however, the promotion of its charge separation is still challenging. Herein, we introduce iodine into Bi2 GdO4 Cl to synthetize I‐doped Bi2 GdO4 Cl (denoted as yI−Bi2 GdO4 Cl, 0≤y≤2). The incorporation of I − ions is found to enhance light absorption and to accelerate charge separation by combining various characterizations such as density functional theory calculation, photoelectrochemical test, electrochemical impedance spectroscopy, photoluminescence spectrum, and open‐circuit voltage decay. The O2 ‐evolving performances of 1I−Bi2 GdO4 Cl with optimized dopant concentration of I − ion and IrO2 loaded 1I−Bi2 GdO4 Cl are tremendously enhanced by ca. 4 and 45 times compared to pristine Bi2 GdO4 Cl. Notably, The O2 evolution rate reaches as high as 154.8 μmol ⋅ h −1 with an apparent quantum efficiency of ∼1.1 % at 420 nm. The synthetic iodine‐doped photocatalyst remains stable after long‐term photoreaction, demonstrating its potential in the field of photocatalysis. Abstract : Iodine‐doped Bi2 GdO4 Cl with a significantly promoted visible‐light‐responsive O2 ‐evolving performance of 154.8 μmol ⋅ h −1 and an apparent quantum efficiency of ∼1.1 % at 420 nm is reported. The incorporation of I − ions causes the extended light absorption and promoted charge separation.